Atypical EEG pattern in children with absence seizures - Silva, Délrio F. [UNIFESP] (1995)
We studied four children with diagnosis of absence seizures (generalized primary epilepsy), and with a generalized delta activity on the EEG during clinical attacks provoked by hyperventilation. The lack of ictal generalized spike-and-wave discharges with a frequency of 3 Hz in our patients, makes this an atypical pattern. All children had complete control of their seizures and disappearance of the EEG changes with valproate. We concluded that generalized delta activity observed on EEG during the hyperventilation in children should not always be considered as a normal finding for age, since it could be an ictal event of an absence seizure.